Work Environment Compensation and Facilities Shape Employee Job Satisfaction: Lingkungan Kerja Kompensasi dan Fasilitas Membentuk Kepuasan Kerja Karyawan - Siska Amalia; I Ketut Budiasa; Komang Sudarsana (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Employee job satisfaction is a key concern in human resource management. Specific Background: PT Indohamafish faces challenges related to working conditions, compensation practices, and workplace facilities that may influence employee satisfaction. Knowledge Gap: Previous studies have reported inconsistent findings regarding the relationships among these variables, highlighting the need for further investigation in the context of PT Indohamafish. Aims: This study examines the relationships between work environment, compensation, work facilities, and employee job satisfaction. A quantitative associative approach was applied using questionnaire data from 43 employees. Results: The findings indicate that work environment (β=0.426; p<0.05), compensation (β=0.352; p<0.05), and work facilities (β=0.479; p<0.05) each show positive and significant relationships with employee job satisfaction. Simultaneously, the three variables are significantly associated with employee job satisfaction (F=36.258; p<0.05). Novelty: This study provides empirical evidence from PT Indohamafish by examining the combined contribution of work environment, compensation, and work facilities to employee job satisfaction. Implications: The findings suggest that improving workplace conditions, providing appropriate compensation, and maintaining adequate facilities may support employee job satisfaction. Highlights • Work environment was positively associated with employee job satisfaction.• Compensation showed a significant relationship with satisfaction levels.• Workplace facilities collectively supported favorable employee perceptions. Keywords Compensation; Employee Job Satisfaction; Human Resource Management; Work Environment; Workplace Facilities